2005
DOI: 10.1113/jphysiol.2005.091835
|View full text |Cite
|
Sign up to set email alerts
|

Hindlimb unweighting for 2 weeks alters physiological properties of rat hindlimb motoneurones

Abstract: We sought to determine whether decreased neuromuscular use in the form of hindlimb unweighting (HU) would affect the properties of innervating motoneurones. Hindlimb weight-bearing was removed in rats for a period of 2 weeks via hindlimb suspension by the tail. Following this the electrophysiological properties of tibial motoneurones were recorded under anaesthesia in situ. After HU, motoneurones had significantly (P < 0.05) elevated rheobase currents, lower antidromic spike amplitudes, lower afterhyperpolariz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
71
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(78 citation statements)
references
References 45 publications
7
71
0
Order By: Relevance
“…Much of this information has been obtained for turtle or cat motoneurons or rat sacrocaudal (tail) motoneurons. Several studies have been performed on the discharge properties of rat hindlimb motoneurons to assess normal function or changes following spinal injury, hindlimb disuse, or hindlimb exercise (Beaumont et al 2004(Beaumont et al , 2008Button et al 2006Button et al , 2008Cormery et al 2005), but direct measurements of PIC activation have not been made in rat hindlimb motoneurons.…”
Section: Introductionmentioning
confidence: 99%
“…Much of this information has been obtained for turtle or cat motoneurons or rat sacrocaudal (tail) motoneurons. Several studies have been performed on the discharge properties of rat hindlimb motoneurons to assess normal function or changes following spinal injury, hindlimb disuse, or hindlimb exercise (Beaumont et al 2004(Beaumont et al , 2008Button et al 2006Button et al , 2008Cormery et al 2005), but direct measurements of PIC activation have not been made in rat hindlimb motoneurons.…”
Section: Introductionmentioning
confidence: 99%
“…Adaptations to an increased or a decreased functional motor demand can be observed as early as after 2-4 wk of an altered motor behavior (Cormery et al 2000(Cormery et al , 2005. Considerable changes in passive or active membrane properties, motoneuron excitability, or firing properties have been established in rat spinal motoneurons as effects of spontaneous running or a locomotor training Gardiner 2002, 2003), in muscle unweighting (Cormery et al 2005) or tetrodoxininduced paralysis (Cormery et al 2000).…”
mentioning
confidence: 99%
“…To reconcile our findings that bullfrogs do not undergo respiratory motor decline following overwintering submergence (Santin and Hartzler, 2016a,b), we hypothesized that bullfrogs would utilize these mechanics during cold-submergence to circumvent the loss of function typically associated with extended disuse in less-active motor systems of non-hibernating mammals (Bonaldo and Sandri, 2013;Cormery et al, 2005;Seki et al, 2007) and certain muscles of heterothermic hibernators (Wickler et al, 1991). We found that underwater lung ventilation cycles, but not buccal oscillations, were present in diving bullfrogs at 20°C, but respiratory muscle activation did not occur during cold-submergence at any time point in this study.…”
Section: Resultsmentioning
confidence: 97%
“…Our findings demonstrate that cold-submergence associated with overwintering produces neuromotor inactivity; a phenomenon that does not usually occur naturally in highly active motor systems as it incurs detrimental consequences to motor function (Banzrai et al, 2016;Bonaldo and Sandri, 2013;Cormery et al, 2005). Muscle plasticity in natural models of inactivity has received considerable attention (Hudson and Franklin, 2002;James et al, 2013;Nowell et al, 2011;Reid et al, 1995;Wickler et al, 1991).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation